A Family History of Diabetes Modifies the Association between Elevated Urine Albumin Concentration and Hyperglycemia in Nondiabetic Mexican Adolescents - Aida Jiménez-Corona; Antonio Ávila-Hermosillo; Robert G. Nelson; Guadalupe Ramírez-López (Journal of Diabetes Research)
We examined the frequency of elevated urine albumin concentration (UAC) and its association with metabolic syndrome (MetS) and metabolic markers in 515 nondiabetic Mexican adolescents stratified by family history of diabetes (FHD). UAC was measured in a first morning urine sample and considered elevated when excretion was ≥20 mg/mL. MetS was defined using International Diabetes Federation criteria. Fasting insulin, insulin resistance, and lipids were evaluated. Multivariate logistic regression was performed. Elevated UAC was present in 12.4% and MetS was present in 8.9% of the adolescents. No association was found between elevated UAC and MetS. Among adolescents with FHD, 18.4% were overweight and 20.7% were obese, whereas, among those without a FHD, 15.9% were overweight and 7.5% were obese. Hyperglycemia was higher in those with elevated UAC than in those without (44.4% versus 5.1%, p=0.003). Hyperglycemia (OR = 9.8, 95% CI 1.6–59.4) and number of MetS components (OR = 4.5, 95% CI 1.5–13.3) were independently associated with elevated UAC. Among female participants, abdominal obesity was associated with elevated UAC (OR = 4.5, 95% CI 1.2–16.9). Conclusion. Elevated UAC was associated neither with MetS nor with any metabolic markers in nondiabetic adolescents. However, FHD modified the association of elevated UAC with hyperglycemia and the number of MetS components.